Desenvolvimento e validação de um método analítico por espectrofotometria UV para quantificação de carvedilol Development and validation of a UV spectrophotometric method to quantify carvedilol - Paola Aline Amarante Borba; Manoela Klüppel Riekes; Rafael Nicolay Pereira; Hellen Karine Stulzer; Debora Dalla Vecchia (Química Nova, 2013)
This paper reports the development and validation of a new analytical method using UV spectrophotometry to quantify carvedilol (CRV) in hydrophilic matrices and raw material. This method was shown to be linear, accurate, precise, robust and to have adequate limits of quantification and detection (LQ and LD, respectively), allowing its use in the dissolution test of hydrophilic matrices. The content of CRV determined through this method was compared with two previously validated methods based on the reference techniques of High Performance Liquid Chromatography (HPLC) and Potentiometric Titrations (PT). ANOVA confirmed the equivalence of these methods, showing no significant differences.